Marketing of engineering services - Scanlon, Brian (Engineering management., 1988)
This title provides guidelines on what should constitute marketing in an engineering environment and how its various aspects can be tackled from a practical standpoint. It is particularly relevant to those aspiring to positions in general management and fills an important gap in the training of professional engineers.